The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/1204328
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigations on Dynamic Response of Hydraulic Cylinder with 3D Spatial Joints considering Radial and Axial Clearances

Abstract: Radial clearance, particularly the axial clearance in the 3D joint of a mechanism owing to the assemblage, manufacturing tolerances, wear, and other conditions, has become a research focus in the field of multibody dynamics in recent years. In this study, a hydraulic cylinder model with 3D clearance joints was constructed by combining various potential contact scenarios. The novelty of this study is that potential contact points between the bearing wall and journal were calculated when the bearing wall circle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 45 publications
(59 reference statements)
0
0
0
Order By: Relevance
“…Joint clearance is a main factor that influences the revolute joints' performance [5][6][7][8]. Existing works [9][10][11][12][13][14][15] have demonstrated that there are radial and axial clearances [i.e., three-dimensional (3D) clearance] in revolute joints between the journal and the bearing. Thus, this paper focuses on the 3D revolute joint with 3D clearance in a linkage mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Joint clearance is a main factor that influences the revolute joints' performance [5][6][7][8]. Existing works [9][10][11][12][13][14][15] have demonstrated that there are radial and axial clearances [i.e., three-dimensional (3D) clearance] in revolute joints between the journal and the bearing. Thus, this paper focuses on the 3D revolute joint with 3D clearance in a linkage mechanism.…”
Section: Introductionmentioning
confidence: 99%